The European Board of Anaesthesiology recommendations for safe medication practice: First update. Issue 1 (January 2017) - Whitaker, David; Brattebø, Guttorm; Trenkler, Stefan; Vanags, Indulis; Petrini, Flavia; Aykac, Zuhal; Longrois, Dan; Loer, Stephan Alexander; Gaszynski, Tomasz; Sipylaite, Jurate; Copaciu, Elena; Cerny, Vladimir; et al.
Abstract : These European Board of Anaesthesiology (EBA) recommendations for safe medication practice replace the first edition of the EBA recommendations published in 2011. They were updated because evidence from critical incident reporting systems continues to show that medication errors remain a major safety issue in anaesthesia, intensive care, emergency medicine and pain medicine, and there is an ongoing need for relevant up-to-date clinical guidance for practising anaesthesiologists. The recommendations are based on evidence wherever possible, with a focus on patient safety, and are primarily aimed at anaesthesiologists practising in Europe, although many will be applicable elsewhere. They emphasise the importance of correct labelling practice and the value of incident reporting so that lessons can be learned, risks reduced and a safety culture developed.